Genotyping Tinea Capitis Fungi and Evaluate the Antifungal Activity of Plant Extract in Vitro (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tinea capitis is a prevalent superficial fungal infection seen in developing nations predominantly in child, theaim of this study included isolating and identification of Tinea capitis fungi isolated from clinical sampleswho attenuate the outpatient clinics and other samples were collected from soils of barber shops, homes andmosques in Babylon / Hilla Province. 120 hairs, scales and soil were 80 clinical samples (hairs and scales),30 soil samples, and 10 hair samples as control group. The results showed that: numbers of dermatophytesfungi were identified based on microscopic and Molecular criteria. T. mentagrophytes, T. tonsurans, M. audounii, M. canis. Also non dermatophytes fungus was Chaetomium globosum. Also three yeast specieswere identified: Candida albicans, Candida parapsilosis, Malassezia spp. based on molecular assays.The antimicrobial activity of plant extract antifungal shown, Capparis spinosa plant has highly antifungalactivity shown inhibition on dermatophytes, followed by Furcraea foetida shown inhibition compare withactivity of Fluconazole in vitro